PJMHS 2022
DOI: 10.53350/pjmhs2216980
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Micro RNAs in Aplastic Anemia Patients Presenting at Tertiary Care Hospital LUMHS, Hyderabad

Abstract: Background: Bone marrow failure that results in pancytopenia causes aplastic anemia clinically. Aim: To determine the frequency of positive microRNAs in plasma of patients with aplastic anemia. Study Design: Descriptive cross-sectional study. Methodology: Aplastic patients were assessed for microRNAs level and patients were considered positive if the level was ≥2 Results: Majority 20(66.7%) of the patients was aged ≤30 years with only 10(33.3%) patients aged above 30 years. There were 22(73.3%) male and 8(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
0
1
Order By: Relevance
“…This study was conducted on Iraqi patients infected with H. pylori and during the study, it was noticed that most patients infected with H. pylori were males, which may give a clue that gender may play a role in H. pylori-related infection, and this observation agrees with many other studies [24,25,26] that confirmed the male predominance of H. pylori. The results showed that there were more electrolyte disturbances in patients infected with H. pylori in comparison with healthy controls.…”
Section: Discussionsupporting
confidence: 87%
“…This study was conducted on Iraqi patients infected with H. pylori and during the study, it was noticed that most patients infected with H. pylori were males, which may give a clue that gender may play a role in H. pylori-related infection, and this observation agrees with many other studies [24,25,26] that confirmed the male predominance of H. pylori. The results showed that there were more electrolyte disturbances in patients infected with H. pylori in comparison with healthy controls.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of Helicobacter Pylori increases with increasing age. But in our study, there was almost no significant difference amongst various age groups, except with slightly reduced frequency in the age group 40-50 years 27,28 (Table 1). This study did not show any significant difference in Helicobacter Pylori regarding other factors like gender, area of abode, cigarette smoking, and the presence of chronic viral hepatitis.…”
Section: 25contrasting
confidence: 61%